Prevent Worm Worms In Children With Clean Water Education At Bangkinang Sustainable Peace Housing - Irfan, Andi; Dessyka Febria,; Arfian, Berlian; Mawaddah, Argya; Afriliia, Cahya (Journal of Community Sustainability, 2024)
Clean water is one of people's needs in everyday life. Providing clean water is closely related to the cleanliness and health status of every individual in society. This outreach activity is aimed at children in the Damai Lestari housing complex to provide education about the importance of using clean water in daily life and one of the causes of worms in children. The aim of this community service is to determine the level of understanding of children around the Damai Lestrai Bangkinang housing complex about clean water and worm infections. The methods used in this community service activity are counseling, presentations and discussions. The results of the service show that the activities run well and smoothly in accordance with the activity plans that have been prepared. In this activity, children gain knowledge about clean water for human health, and it is hoped that this outreach can increase children's awareness of consuming clean water, living a clean and healthy lifestyle thereby reducing the number of worms in children and other diseases caused by it. by the environment.